2020
DOI: 10.3390/technologies8030045
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Industrial Scale Cannabis Extraction

Abstract: Cannabis is a flowering plant that has long been used for medicinal, therapeutic, and recreational purposes. Cannabis contains more than 500 different compounds, including a unique class of terpeno-phenolic compounds known as cannabinoids. Δ9-tetrahydrocannabinol (THC) and cannabidiol (CBD) are the most extensively studied cannabinoids. They have been associated with the therapeutic and medicinal properties of the cannabis plant and also with its popularity as a recreational drug. In this paper, an industrial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…MW pre-treatments on rosemary leaves resulted in almost two times the phytochemical concentration during storage compared to the untreated leaves [ 50 ]. Phytocannabinoid extraction with the assistance of MW shows a significant improvement of the process output [ 51 , 52 , 53 , 54 ]. To prompt the drying process and to improve the polyphenol, cannabinoid, and terpene profile of cannabis, MW heating could be an ideal pre-treatment.…”
Section: Postharvest Operations Involved In Cannabismentioning
confidence: 99%
“…MW pre-treatments on rosemary leaves resulted in almost two times the phytochemical concentration during storage compared to the untreated leaves [ 50 ]. Phytocannabinoid extraction with the assistance of MW shows a significant improvement of the process output [ 51 , 52 , 53 , 54 ]. To prompt the drying process and to improve the polyphenol, cannabinoid, and terpene profile of cannabis, MW heating could be an ideal pre-treatment.…”
Section: Postharvest Operations Involved In Cannabismentioning
confidence: 99%
“…Furthermore, the antioxidant capacities in terms of DPPH inhibition, ABTS inhibition, and FRAP capacity were also increased, as previously mentioned ( Table 1 ). The main downsides of the organic solvent approach are related to unsuitable materials, such as fats, waxes, and pigments, which dissolve along with the cannabinoids, as well as the extraction temperatures, which frequently cause the destruction of heat-sensitive compounds during processing [ 8 , 10 , 16 , 34 ]. In previous studies, selection criteria were based on solvent extraction, such as ethanol or methanol combined with microwave extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the effects of microwave extraction processing differ from those of the organic solvent extraction method due to alterations in the cell structure by electromagnetic radiation during extraction [ 7 ]. Moreover, advances in microwave extraction have led to the development of cutting-edge processes, including vacuum microwave hydrodistillation, microwave Soxhlet extraction, microwave-assisted Clevenger distillation, etc., which are environmentally friendly methods that can be used to reduce energy use, time required for extraction, solvent use, and waste [ 10 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different conventional extraction methods, including Soxhlet extraction, maceration, and dynamic maceration, have been employed to extract phytochemicals from Cannabis [ 68 , 75 , 76 , 80 , 82 ]. However, studies have also revealed the caveats of using conventional extraction methods, such as the extraction of unwanted substances and degradation of heat-sensitive compounds due to extraction under high temperature [ 84 ]. As cannabinoids, phenolic compounds, and terpenes are the three main classes of secondary metabolites in Cannabis , the conventional extraction of these main classes is discussed further in the following subsections.…”
Section: Current Techniques For Extraction Of Phytochemicals From ...mentioning
confidence: 99%